Aqueous Two-Phase Systems for Bioprocess Development for the Recovery of Biological Products - Rito-Palomares, Marco; Benavides, Jorge (Springer International Publishing : Imprint: Springer, 2017)
This comprehensive and unique text presents a full overview of downstream processing useful for those new to the concept as well as professionals with experience in the area. The history and theoretical principles of Aqueous Two-Phase Systems (ATPS) are covered in depth. Information on ATPS characterization and application is included, and ATPS equilibria and system parameters that have significant effect on partition behavior are studied. Aqueous Two-Phase Systems for Bioprocess Development for the Recovery of Biological Products addresses specific applications of ATPS for the recovery and partial purification of high molecular weight compounds such as proteins, nucleic acids and polysaccharides, particulate bioproducts such as cells and organelles and low molecular weight compounds. Non-conventional strategies involving ATPS such as affinity systems, continuous liquid-liquid fractionation stages and the recovery from plant extracts are presented. Economic analysis of the application of ATPS in comparison to other fractionation techniques, particularly liquid chromatography, is considered, as are opportunity and current trends in the ATPS research area. Each chapter utilizes the contributors' experimental expertise in traditional and non-conventional ATPS strategies, as well as analysis of areas of opportunity and perspectives on the development and future applications of ATPS in both the lab and larger scale operations. The result is a thorough and singular overview of ATPS which has not been matched by any other text on the market. .
Keywords: Chemistry.; Food -- Biotechnology.; Organic chemistry.; elektronické knihy; electronic books